Impact of fatigue on nursing care rationing in paediatric haematology and oncology departments - a cross-sectional study - Beata Jankowska-Polańska; Monika Czyrniańska; Kathie Sarzyńska; Natalia Świątoniowska-Lonc; Mariusz Chabowski (BMC, 2021)
Abstract Background Rationing of nursing care is a relatively new concept. It refers to an error of omission and has a direct influence on the quality of nursing care and treatment outcomes. Nurses who experience chronic fatigue often fail to perform their duties properly, which may lead, for instance, to medical errors attributed to impaired judgment. Therefore, it is necessary to identify factors which give rise to fatigue, leading to rationing of nursing care, and develop strategies to eliminate them. The primary objective of the study was to assess the impact of fatigue on nursing care rationing in paediatric haematology and oncology departments. The secondary objective of this study was to identify the factors, which may influence the nursing care rationing. Methods The study was conducted among 95 nurses (aged between 23 and 58 years) workinginthe Department of Paediatric Oncology, Haematology and Bone Marrow Transplantation of the University Teaching Hospital in Wroclaw. Participation in the study was voluntary and anonymous. Our own sociodemographic questionnaire, the Basel Extent of Rationing of Nursing Carequestionnaire and the modified fatigue impact scale (MFIS) were used in the study. Results The level of fatigue among the nurses participating in the study, as measured by the MFIS, was high, namely 28.97 ± 16.78. It was found that the fatigue of the nurses influenced most often the psycho-social dimension of QoL (1.78 ± 1.05), and least often - cognitive (1.24 ± 0.78). A correlation analysis showed that all aspects of fatigue had a statistically significant positive impact on care rationing (p < 0.05), i.e. the greater the fatigue, the higher the level of care rationing. A regression analysis showed that a 12-h shift pattern was an independent predictor of the level of care rationing (r = 0.771, p < 0.05). Conclusions Nurses working in paediatric haematology departments report a high level of fatigue. Work pattern is an independent determinant of nursing carerationing. A high level of nursing care rationing was found for nurses working 12-h shifts. Trial registration The study was approved by the Bioethics Committee of the Wroclaw Medical University, Poland (February 8th 2019, No. 205/2019).